REFINE (Rapid Feedback for quality Improvement in Neonatal rEsuscitation): an observational study of neonatal resuscitation training and practice in a tertiary hospital in Nepal - Rejina Gurung; Abhishek Gurung; Omkar Basnet; Joar Eilevstjønn; Helge Myklebust; Sakina Girnary; Shree Krishna Shrestha; Dela Singh; Laxman Bastola; Prajwal Paudel; Sandhya Baral; Ashish KC (BMC, 2020)
Abstract Background Simulation-based training in neonatal resuscitation is more effective when reinforced by both practice and continuous improvement processes. We aim to evaluate the effectiveness of a quality improvement program combined with an innovative provider feedback device on neonatal resuscitation practice and outcomes in a public referral hospital of Nepal. Methods A pre- and post-intervention study will be implemented in Pokhara Academy of Health Sciences, a hospital with 8610 deliveries per year. The intervention package will include simulation-based training (Helping Babies Breathe) enhanced with a real-time feedback system (the NeoBeat newborn heart rate meter with the NeoNatalie Live manikin and upright newborn bag-mask with PEEP) accompanied by a quality improvement process. An independent research team will collect perinatal data and conduct stakeholder interviews. Discussion This study will provide further information on the efficiency of neonatal resuscitation training and implementation in the context of new technologies and quality improvement processes. Trial registration https://doi.org/10.1186/ISRCTN18148368 , date of registration-31 July 2018